Characterization of phase changes during fabrication of copper alloys, crystalline and non-crystalline, prepared by mechanical alloying (2016)
The manufacture of alloys in solid state has many differences with the conventional melting (casting) process. In the case of high energy milling or mechanical alloying, phase transformations of the raw materials are promoted by a large amount of energy that is introduced by impact with the grinding medium; there is no melting, but the microstructural changes go from microstructural refinement to amorphization in solid state. This work studies the behavior of pure metals (Cu and Ni), and different binary alloys (Cu-Ni and Cu-Zr), under the same milling/mechanical alloying conditions. After high-energy milling, X ray diffraction (XRD) patterns were analyzed to determine changes in the lattice parameter and find both microstrain and crystallite sizes, which were first calculated using the Williamson-Hall (W-H) method and then compared with the transmission electron microscope (TEM) images. Calculations showed a relatively appropriate approach to observations with TEM; however, in general, TEM observations detect heterogeneities, which are not considered for the W-H method. As for results, in the set of pure metals, we show that pure nickel undergoes more microstrain deformations, and is more abrasive than copper (and copper alloys). In binary systems, there was a complete solid solution in the Cu-Ni system and a glass-forming ability for the Cu-Zr, as a function of the Zr content. Mathematical methods cannot be applied when the systems have amorphization because there are no equations representing this process during milling. A general conclusion suggests that, under the same milling conditions, results are very different due to the significant impact of the composition: nickel easily forms a solid solution, while with a higher zirconium content there is a higher degree of glassforming ability.